A two‐dimensional mixed‐valence CuII/CuI coordination polymer constructed from 2‐(pyridin‐3‐yl)‐1H‐imidazole‐4, 5‐dicarboxylate. Issue 8 (22nd July 2016) - Zhang, Li-Yang; Lu, Li-Ping; Feng, Si-Si
Abstract : A novel two‐dimensional Cu II /Cu I coordination polymer, with a (2, 3)‐connected topological network, was assembled from 2‐(pyridin‐3‐yl)‐1 H ‐imidazole‐4, 5‐dicarboxylate. Susceptibility measurements indicate weak ferromagnetic coupling. Abstract : Coordination polymers are a thriving class of functional solid‐state materials and there have been noticeable efforts and progress toward designing periodic functional structures with desired geometrical attributes and chemical properties for targeted applications. Self‐assembly of metal ions and organic ligands is one of the most efficient and widely utilized methods for the construction of CPs under hydro(solvo)thermal conditions. 2‐(Pyridin‐3‐yl)‐1 H ‐imidazole‐4, 5‐dicarboxylate (HPIDC 2− ) has been proven to be an excellent multidentate ligand due to its multiple deprotonation and coordination modes. Crystals of poly[aquabis[μ3 ‐5‐carboxy‐2‐(pyridin‐3‐yl)‐1 H ‐imidazole‐4‐carboxylato‐κ 5 N 1, O 5 : N 3, O 4 : N 2 ]copper(II)dicopper(I)], [Cu II Cu I 2 (C10 H5 N3 O4 )2 (H2 O)] n, (I), were obtained from 2‐(pyridin‐3‐yl)‐1 H ‐imidazole‐4, 5‐dicarboxylic acid (H3 PIDC) and copper(II) chloride under hydrothermal conditions. The asymmetric unit consists of one independent Cu II ion, two Cu I ions, two HPIDC 2− ligands and one coordinated water molecule. The Cu II centre displays a square‐pyramidal geometry (CuN2 O3 ), with two N, O ‐chelating HPIDC 2− ligands occupying the basal plane in a trans geometry and one O atom from a coordinated water molecule in the axial position. The Cu I atoms adopt three‐coordinated Y‐shaped coordinations. In each [CuN2 O] unit, deprotonated HPIDC 2− acts as an N, O ‐chelating ligand, and a symmetry‐equivalent HPIDC 2− ligand acts as an N‐atom donor via the pyridine group. The HPIDC 2− ligands in the polymer serve as T‐shaped 3‐connectors and adopt a μ3 ‐κ 2 N, O :κ 2 N ′, O ′:κ N ′′‐coordination mode, linking one Cu II and two Cu I cations. The Cu cations are arranged in one‐dimensional –Cu1–Cu2–Cu3– chains along the [001] direction. Further crosslinking of these chains by HPIDC 2− ligands along the b axis in a –Cu2–HPIDC 2− –Cu3–HPIDC 2− –Cu1– sequence results in a two‐dimensional polymer in the (100) plane. The resulting (2, 3)‐connected net has a (12 3 )2 (12)3 topology. Powder X‐ray diffraction confirmed the phase purity for (I), and susceptibilty measurements indicated a very weak ferromagnetic behaviour. A thermogravimetric analysis shows the loss of the apical aqua ligand before decomposition of the title compound.